A research-informed model for corporate social responsibility: Towards accountability to impacted stakeholders - Dyann Ross (International Journal of Corporate Social Responsibility (JCSR), 2017)
An Australian case study is presented of an ongoing conflict between Alcoa World Alumina, a multi-national mining company and the impacted stakeholders of Yarloop, a small rural community in Western Australia. The conflict has been subject to research by the author since the early 2000s and is the impetus for developing a model for corporate social responsibility (CSR). The model emphasises engaging impacted stakeholders in dialogue with powerful stakeholders to achieve social justice. This involves a three way set of relationships with key people in leadership positions from the relevant government departments, the corporation's management group and the impacted stakeholders. The model is premised on an ethic of love approach which utilises the ideas of social justice, social sustainability, and the social pre-cautionary principle. An outline is presented of these ideas as well as a set of inter-linked strategies which are responsive to power inequalities in conflict situations. The ideas and strategies can guide efforts to address the social costs incurred by the impacted community stakeholders. This will involve a discerning commitment to work towards accountable government, sustainable business practices and social justice for impacted stakeholders. The approach requires a cultural shift in the business sector, and wider society, to equally value people, place and profit.
Keywords: 650; Social work; Corporate social responsibility; Dialogue; Impacted stakeholders; Social justice; Social precautionary principle; Social sustainability; Ethic of love; Warrants; Accountability